2019
DOI: 10.20473/ijtid.v7i4.7362
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Soil-Transmitted Helminthiasis Among Elementary Children in Sorong District, West Papua

Abstract: Soil transmitted helminthiasis are common in the world and cause illness, especially in developing countries. It can cause infection in humans by contact with parasitic eggs or larvae that live in moist and warm soil. Soil-transmitted helminthiasis is often caused by Ascaris lumbricoides, Trichuris trichiura, Ancylostoma duodenale, and Necator americanus. In Indonesia, Soil transmitted helminthiasis prevalence is still high in some places. The tropical climate and high humidity support for the development of w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
12
1
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 12 publications
1
12
1
2
Order By: Relevance
“…4 As many as 60% to 80% of Indonesia's population is infected by STH, 1 the prevalence is even higher in certain regions. 1,3,5 Primary school age is a high-risk group to be infected with STH. 5 This is due to poor immunity and lack of awareness to live clean and healthily.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…4 As many as 60% to 80% of Indonesia's population is infected by STH, 1 the prevalence is even higher in certain regions. 1,3,5 Primary school age is a high-risk group to be infected with STH. 5 This is due to poor immunity and lack of awareness to live clean and healthily.…”
Section: Introductionmentioning
confidence: 99%
“…1,3,5 Primary school age is a high-risk group to be infected with STH. 5 This is due to poor immunity and lack of awareness to live clean and healthily. 6 Especially in Bali, the prevalence of STH infections in rural areas is still high.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…His description referred to the kris culture of the Surakarta Palace court. The ladrang and gayaman sheath, and the tunggak semi hilt (Yuwono 2012) are characteristic of the Surakarta kris. The Surakarta kris is believed to have be conceptualized by PB III in 1749 -1788, to differentiate it from the tangguh tengahan kris of the Kasunanan Kartasura (1680 -1745).…”
Section: Introductionmentioning
confidence: 99%
“…However, high environmental humidity has a significant effect on the development of worm eggs. Study results from Yuwono, Pasulu, Husada, & Basuki (2019) found that children in Papua infected with STH mostly lived in areas with high humidity.…”
Section: Introductionmentioning
confidence: 99%